Individual variation over time in piglet´s reactions to early handling and its association to weight gain - de Oliveira, Daiana; Keeling, Linda Jane; Paranhos da Costa, Mateus José Rodrigues [UNESP] (My University, 2019)
Individual variation in how animals react in challenging situations is an important topic since it relates to different coping strategies. Previous work with piglets has focused mainly on the backtest, which does not take into account variation within an individual in how it adapts to the challenge. Our aim was to assess individual pig's reactions to human early handling by using different measures of individual variation, including how reactions by the same piglet change over time, and how these measures relate to piglet´s weight gain. We stroked 66 piglets on their back for two minutes each day, starting at five days of age. Piglets were scored immediately after each handling session (scale 1–4, lowest reactive to highest reactive), totalling 15 scored sessions. Individual variation was calculated by averaging the scores (AS) of all sessions and by calculating the b-coefficient (b) of linear regressions in order to assess changes in individuals over time. We assessed the relationship between these measures (AS and b) and piglet growth at 5, 9 and 12 weeks of age using generalized mixed models. We found a large variation in piglet scores, and also that there was a continuum on how individual score within a piglet varied over time (b). This measure (b) was related to the piglet's overall weight gain (0–12 weeks of age) in that individuals who became calmer over time gained more weight than those who became more reactive over time (F = 3.87, P = 0.05). AS was positively related to weight gain, in that for each unit of increase in the reactive score, there was an increase of 1.3 kg in body weight at 9 weeks of age (F = 3.79, P = 0.05). We conclude that piglets show a large individual variation in their reaction to human handling, not only in the magnitude of their reactivity which has been shown previously, but also how their reactions change over time. For extreme individuals, this change probably implies habituating or sensitizing to the repeating handling. The change over time (b) was associated with weight gain, and we suggest that this association might be modulated by individual traits. We also suggest that individual traits interact with piglet's developmental plasticity, which are likely influencing their ontogeny, and in turn influence the further development of the piglet. In future studies developmental plasticity measured by changes over time should be considered when assessing individual variation.
Keywords: Behaviour; Developmental plasticity; Ontogeny; Performance; Pigs; Tactile stimulation